Multicolor photoluminescence of Cu14 clusters modulated using surface ligands - Jana, Arijit; Duary, Subrata; Das, Amitabha; Kini, Amoghavarsha Ramachandra; Acharya, Swetashree; Machacek, Jan; Pathak, Biswarup; Base, Tomas; Pradeep, Thalappil (Chemical science, 2024)
Copper nanoclusters exhibit unique structural features and their molecular assembly results in diverse photoluminescence properties. In this study, we present ligand-dependent multicolor luminescence observed in a Cu14 cluster, primarily protected by ortho-carborane-9,12-dithiol (o-CBDT), featuring an octahedral Cu6 inner kernel enveloped by eight isolated copper atoms. The outer layer of the metal kernel consists of six bidentate o-CBDT ligands, in which carborane backbones are connected through μ3-sulphide linkages. The initially prepared Cu14 cluster, solely protected by six o-CBDT ligands, did not crystallize in its native form. However, in the presence of N,N-dimethylformamide (DMF), the cluster crystallized along with six DMF molecules. Single-crystal X-ray diffraction (SCXRD) revealed that the DMF molecules were directly coordinated to six of the eight capping Cu atoms, while oxygen atoms were bound to the two remaining Cu apices in antipodal positions. Efficient tailoring of the cluster surface with DMF shifted its luminescence from yellow to bright red. Luminescence decay profiles showed fluorescence emission for these clusters, originating from the singlet states. Additionally, we synthesized microcrystalline fibers with a one-dimensional assembly of DMF-appended Cu14 clusters and bidentate DPPE linkers. These fibers exhibited bright greenish-yellow phosphorescence emission, originating from the triplet state, indicating the drastic surface tailoring effect of secondary ligands. Theoretical calculations provided insights into the electronic energy levels and associated electronic transitions for these clusters. This work demonstrated dynamic tuning of the emissive excited states of copper nanoclusters through the efficient engineering of ligands.